Systematics of the genus Abelia (Caprifoliaceae) in Mexico - Villarreal-Quintanilla, José Á.; Villaseñor-Ríos, José Luis; Estrada-Castillón, Eduardo (Instituto de Ecología, A.C., 2013)
The genus Abelia (Caprifoliaceae) includes a set of shrubby plants distributed in the montane temperate regions of eastern Asia and America. The genus is characterized by its persistent sepals, its funnelform or tubular corolla and its indehiscent trilocular capsule. In America all the species known for this genus are restricted to Mexico, and taxonomically they are included in the section Vesalea. A cladistic analysis, using 20 morphological, anatomical, and palynological characters was carried out to evaluate the monophyly of the section Vesalea. All the species of this section were included as the ingroup; in addition, 12 Asiatic abelias pertaining to other sections of the genus were included as outgroup and Kolkwitzia amabilis was used as the functional outgroup. The analysis supports the monophyly of section Vesalea, placed as the sister group of several species of section Abelia. The taxonomy of the Mexican taxa comprises five known species and two new proposed varieties: A. coriacea var. coriacea, A. coriacea var. subcoriacea Villarreal, A. floribunda var. floribunda, A. floribunda var. foliacea Villarreal A. grandifolia, A. mexicana and A. occidentalis. Important data on the geographical distribution and the environments where the species occur are provided, as well as descriptions for each one and a key to their identification.